Public support for government-led skin cancer prevention in Aotearoa New Zealand: findings from a national survey - Bronwen McNoe; Andrew Gray; Ryan Gage; Ella Iosua; Rana Peniamina; Louise Signal (New Zealand Medical Journal, 2026)
aim: We aimed to assess public support for skin cancer prevention policies and examine how responsibility for prevention is perceived across key societal actors. methods: A nationally representative survey of adults in Aotearoa New Zealand assessed support for society wide regulatory measures, school based interventions and increased public investment in skin cancer prevention, as well as perceived responsibility across government, institutional and community actors. results: We received 1,635 responses, including 385 participants identifying as Māori (23.5%, unweighted) and 368 participants identifying as Pacific peoples (22.5%, unweighted). Support for skin cancer prevention policies was high across all domains. Overall support was 90.1% for government funding of a national SunSmart programme, 91.5% for funding a SunSmart school programme, 90.4% for compulsory school sun-protection policies and 87.3% for Education Review Office (ERO) checks of school sun-protection practices. Support was also high for improving sunscreen affordability (89.1%), regulating sunscreen as a therapeutic product (80.7%) and banning commercial sunbed services (72.5%). Majority support was observed across voting intention. Between 91.4% and 96.3% of respondents assigned at least some responsibility for skin cancer prevention to each actor examined, with schools and government most frequently identified as having a high level of responsibility. conclusion: There is strong public support for government led, structural approaches to skin cancer prevention across demographic and political groups of particular interest, indicating high public acceptability and scope to advance effective and equitable prevention policy.